2013
DOI: 10.1073/pnas.1220271110
|View full text |Cite
|
Sign up to set email alerts
|

E3 ligase WWP2 negatively regulates TLR3-mediated innate immune response by targeting TRIF for ubiquitination and degradation

Abstract: Recognition of viral double-stranded RNA by Toll-like receptor 3 (TLR3) triggers activation of the transcription factors NF-κB and interferon regulated factor 3, leading to induction of type I interferons and proinflammatory cytokines. TIR-domain-containing adapter-inducing interferon-β (TRIF) is an adapter protein required for TLR3-mediated signaling. Here we identified the E3 ubiquitin ligase WW domaincontaining protein 2 (WWP2) as a TRIF-associated protein by biochemical purification. WWP2 mediated K48-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 26 publications
(34 reference statements)
1
78
0
1
Order By: Relevance
“…Finally, mouse gene-knockout studies demonstrated that Nap1 is not required for TLR3/4-mediated innate immune responses (32). Previously, we reported that another E3 ubiquitin ligase, WWP2, also targets TRIF for K48-linked polyubiquitination and proteasomal degradation (16). However, WWP2 functions differently with TRIM38.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Finally, mouse gene-knockout studies demonstrated that Nap1 is not required for TLR3/4-mediated innate immune responses (32). Previously, we reported that another E3 ubiquitin ligase, WWP2, also targets TRIF for K48-linked polyubiquitination and proteasomal degradation (16). However, WWP2 functions differently with TRIM38.…”
Section: Discussionmentioning
confidence: 98%
“…Mouse anti-TRIF, mouse anti-IkBa, mouse anti-TAB2, and rabbit anti-TAB3 were described previously (11,(16)(17)(18).…”
Section: Reagents and Absmentioning
confidence: 99%
“…Several sensors and mediators of IFN synthesis and signaling modify their stability or functionality by ubiquitination. These include MyD88, TRIF or nuclear IRF3, degraded after the action of several E3 ligases, whose increase reduces IFN synthesis (Xue et al, 2012; Yang et al, 2013a; Wang et al, 2015). In contrast, USP13 (Ubiquitin Specific Peptidase 13) is a DUB that deubiquitinates STAT1 to avoid degradation and potentiate IFN signaling (Yeh et al, 2013).…”
Section: Protein-modulated Control Of the Antiviral Responsementioning
confidence: 99%
“…Pellino1 promotes K63-linked polyubiquitination of RIP1 and thus selectively facilitates TLR3-mediated activation of NF-κB and induction of pro-inflammatory cytokines [33]. In contrast, the E3 ligases WWP2, TRIM38, and Nrdp1 catalyze K48-linked ubiquitination and induce the proteasome-dependent degradation of TRIF and MyD88, respectively, turning down TLR-mediated signaling [34][35][36].…”
Section: Tlr-mediated Signalingmentioning
confidence: 99%